The solution to the expression (-0.75x + 6) -(2.5x -1.9) is -3.25x + 7.9
From the question, we have the following parameters that can be used in our computation:
(-0.75x + 6) -(2.5x -1.9)
Open teh brackets
So, we have
(-0.75x + 6) -(2.5x -1.9) = -0.75x + 6 -2.5x + 1.9
Evaluate the like terms
So, we have
(-0.75x + 6) -(2.5x -1.9) = -3.25x + 7.9
Hence, the solution is -3.25x + 7.9
Read more about expression at
#SPJ6
problem given: (-0.75x + 6) -(2.5x -1.9)
distribute: -0.75x+6 -2.5x-1.9
combine like terms: -0.75x-2.5x= -3.25x ; 1.9+6=7.6
solution: -3.25x+7.6
Answer:
The number is 48
Step-by-step explanation:
The number be x
Quotient of the number and 3 : x/3
Ten less the quotient of the number and x : x/3 -10
Answer:
Quotient of a number and 3 = x/3
Ten less the quotient of a number and 3 will equal 6
So...
10 - x/3 = 6
+ x/3 +x/3
10 = x/3 +6
-6 - 6
3 × 4=(x/3) × 3
12 = x
B. (3/4, -9/4)
C. (3, 4)
D. (-9/4, 0)
Answer:
A. 4/3, -4 I believe is the correct answer.
Step-by-step explanation:
x+y=25
x=2y+7
x+y=25
(2y+7)+y=25
3y+7=25
-7. -7
3y=18
÷3. ÷3
y=6
x=19
19 and 6
B. 4761 cm cubed
C. 2484 cm cubed
D. 972 cm cubed
Origin
Formula
Term